2021
DOI: 10.1186/s12917-021-02933-7
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella sp.-related infectious spondylitis in a bearded dragon (Pogona vitticeps)

Abstract: Background Spondylitis is an inflammation of the vertebrae that leads to a destructive process with exuberant new bone formation. Osteomyelitis can produce a distortion of the bone architecture, degenerative joint changes and ankyloses of adjacent vertebrae. In reptiles, intervertebral discs are absent, so the term discospondylitis is not used. In lizards, vertebral lesions have not been well studied. The present paper describes the first case of Klebsiella sp.-related spondylitis in a pet liza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous research indicates that the cloacal microbiome serves to deposit microbes with antifungal capabilities on eggshells during oviposition 24 , and members of the Enterobacteriaceae have antifungal properties in this (unpublished data) and other systems 48 50 . However, we also note that some of the Enterobacteriaceae detected here (e.g., Klebsiella ) represent genera that include pathogens of other reptiles 51 , 52 . Helicobacteraceae is the next most abundant taxon in the community, and certain Helicobacteraceae species are highly host-specific and have a long-term relationship with reptiles 53 .…”
Section: Discussionmentioning
confidence: 65%
“…Previous research indicates that the cloacal microbiome serves to deposit microbes with antifungal capabilities on eggshells during oviposition 24 , and members of the Enterobacteriaceae have antifungal properties in this (unpublished data) and other systems 48 50 . However, we also note that some of the Enterobacteriaceae detected here (e.g., Klebsiella ) represent genera that include pathogens of other reptiles 51 , 52 . Helicobacteraceae is the next most abundant taxon in the community, and certain Helicobacteraceae species are highly host-specific and have a long-term relationship with reptiles 53 .…”
Section: Discussionmentioning
confidence: 65%
“…This is the first report of ectopic bone formation in a bearded dragon. The clinical sign of joint swellings has been reported in the literature with different etiologies: osteodystrophy/metabolic bone disease, osteomyelitits, trauma, neoplasia (i.e., chondroma), septic arthritis, and gout/pseudogout (Tocidlowski et al, 2001;Girling and Fraser, 2007;Perpi ˜na´n, 2009;Reavill, 2014;Vaillard et al, 2021;Vetere et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria were identified as Klebsiella oxytoca. Because this bacterium is considered an opportunistic pathogen arising from normal flora on snake skin, the mass was suspected to be an abscess [12,13]. Furthermore, after referring to human cases, we found that several reports have indicated that abscess-mimicking tumors and tumor-mimicking abscesses can cause confusion in differential diagnoses [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%